Beton Ramah Lingkungan menggunakan Serat Serabut Kelapa sebagai Bahan Tambah Campuran Beton (Indonesian Journal of Civil Engineering Study, 2026)
Concrete is the main construction material widely used throughout the world. The development of concrete technology demands better performance, both in terms of mix composition and the addition of additives to enhance concrete strength. This has led to the idea of finding additive materials that can improve concrete strength, one of which is by using coconut fiber as an additional material. This study aims to determine the compressive strength, flexural strength, and split tensile strength of concrete with the addition of coconut fiber at proportions of 0%, 0.7%, and 1.5% of the specimen weight. The study used a water–cement ratio (w/c) of 0.52, and the tests were conducted at the ages of 7 and 28 days. The research methodology used was experimental, with 18 cylindrical and 9 beam specimens. The average compressive strength test results at 12 days for concrete with 0%, 0.7%, and 1.5% coconut fiber additions were 21.27 MPa, 13.10 MPa, and 8.54 MPa, respectively. The estimated 28-day compressive strength results were 25.4 MPa for 0%, 16.2 MPa for 0.7%, and 10.6 MPa for 1.5% fiber content. The average split tensile strength results at 12 days for 0%, 0.7%, and 1.5% fiber content were 0.98 MPa, 1.15 MPa, and 0.75 MPa, respectively. The estimated 28-day split tensile strengths were 1.16 MPa, 1.43 MPa, and 0.92 MPa, respectively. The average flexural strength test results at 7 and 28 days for 0%, 0.7%, and 1.5% coconut fiber additions were 4.62 MPa, 3.16 MPa, and 2.94 MPa, respectively.
Keywords: Coconut Fiber; Compressive Strength; Concrete; Flexural Strength; Splitting Tensile Strength